Valuation of Company Merger from the Shareholders' Point of View - Christian Toll; Thomas Hering (Amfiteatru Economic Journal, 2017)
By means of a company merger formerly legally and economically independent companies are tied up to an economic entity. To order the financial state of affairs after the merger, the current shareholders must revalue their stake in the merged company. The interest is focused on the valuation of shares and, consequently, on the allocation of the future economic benefits of the merged company to each owner. Despite the apparent relevance of company mergers in practice, the scientific literature deals with this topic only in an unsatisfying manner. After some early simple model-oriented approaches with the aim to define an ideal exchange ratio, the valuation problem of a merger was taken up again not earlier than in Hering (2004). Based on his considerations, the aim of our paper is to extend and generalize the valuation methods for a company merger and foremost to set the algebra for the computation of the critical share by using maximization of wealth as target function on a firm foundation. We assign a certain marginal quota to the shareholders representing the minimum share in the merged company which puts them in a financial position no worse than compared to the going concern basis. For this reason, we introduce the state marginal quota model as an innovative valuation approach that considers both existing market imperfections and individual expectations of a specific shareholder. To pinpoint our key finding: If private financial redistributions are available, our extended and generalized model shows that the marginal quota ?* in question cannot be “trivially” obtained as a ratio of utilities. Instead, it is essential to consider the private decision field of a shareholder to allow a restructuring of the dividend payout stream offered by the merged company in order to reach at least a level of utility which is comparable to the state before the merger.
Keywords: C61; G31; G34; 330; business valuation; company merger; decision function; shareholder; marginal quota; maximization of wealth